Определение жесткостных параметров породных слоев методом граничных элементов применительно к горно-геологическим условиям шахт западного Донбасса - Яворский, А.В. (Геотехническая механика, 2011)
Описано алгоритм побудови функції жорсткості шаруватого масиву, яка є необхідною
для визначення зміщень та деформацій усередині масиву, що підроблюється, та на його
поверхні. В основі алгоритму – аналітичний розв`язок диференціального рівняння
пластичності для однорідного середовища, що отриманий Р.А. Муллером, та чисельний
розв`язок, який здійснено методом граничних елементів. The algorithm of creating the hardness function of stratified massif necessary for determining
displacements and deformations inside the underworking massif and on its surface has been described. The algorithm is based on the analytical solution of differential equation of elasticity for
homogeneous environment got by R.A. Muller and on the numerical solution made by the method of boundary elements used.